2014
DOI: 10.1177/0956797614544511
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Morphometric Changes Uniquely Predict Children’s Reading Acquisition

Abstract: This study examined whether variations in brain development between kindergarten and Grade 3 predicted individual differences in reading ability at the latter time point. Structural MRI measurements indicated that increases in volume of two left temporo-parietal white matter clusters are unique predictors of reading outcome at Grade 3. Using diffusion MRI, the larger of these two clusters was identified as a location where fibers of the long segment of arcuate fasciculus and superior corona radiata intersect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 44 publications
6
82
0
2
Order By: Relevance
“…Another study also reported significantly predicting ASD symptom severity using rs-fcMRI, but they did not report the amount of variance explained by their models (43). Previous studies with other populations, including individuals with depression (26), dyslexia (27), alcoholism (28), and academic difficulties (29,30), have further shown that brainbased features can add additional predictive power to behavioral measures. For example, using a similar cross-validation procedure, Supekar et al (29) were able to predict individuals' responses to math tutoring above and beyond the variance explained by behavior using structural and functional MRI data collected before tutoring.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Another study also reported significantly predicting ASD symptom severity using rs-fcMRI, but they did not report the amount of variance explained by their models (43). Previous studies with other populations, including individuals with depression (26), dyslexia (27), alcoholism (28), and academic difficulties (29,30), have further shown that brainbased features can add additional predictive power to behavioral measures. For example, using a similar cross-validation procedure, Supekar et al (29) were able to predict individuals' responses to math tutoring above and beyond the variance explained by behavior using structural and functional MRI data collected before tutoring.…”
Section: Discussionmentioning
confidence: 93%
“…Hippocampal gray matter volume predicted 20.25% of the variance in individuals' math improvement, and connectivity between the basal ganglia and hippocampus predicted 56.25% of the variance. Myers et al (30) found that white matter morphometry, in conjunction with baseline behavioral measures, predicted 56% of the variance in reading impairment at a later date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a sample of 58 children between ages 5-9, white matter volume changes within the left arcuate fasciculus predict reading outcomes during the developmental period when children become fluent readers [46]. Similarly, the volume of the left arcuate fasciculus and superior corona radiata assessed in 38 children between five-and six-years predicted third grade reading abilities [47].…”
Section: The Role Of the Arcuate Fasciculus In Reading And Developmenmentioning
confidence: 95%
“…Notably, white matter is highly plastic during development including the school years where there is age-related maturation [8] and changes in response to genetic and experiential factors [9]. One of the experiential factors that are shown to impact white-matter maturation is the process of reading acquisition [10][11][12]. The goal of the current paper is to examine the developmental progression of white-matter pathways as they are related to reading stages associated with reading acquisition (i.e., 3-6 year olds), reading refinement (6-14 years), and reading maintenance (14-21 year olds).…”
mentioning
confidence: 99%